Investigation of the molecular similarity in closely related protein systems: The PrP case study. Issue 10 (6th August 2015) - Storchi, Loriano; Paciotti, Roberto; Re, Nazzareno; Marrone, Alessandro
ABSTRACT The amyloid conversion is a massive detrimental modification affecting several proteins upon specific physical or chemical stimuli characterizing a plethora of diseases. In many cases, the amyloidogenic stimuli induce specific structural features to the protein conferring the propensity to misfold and form amyloid deposits. The investigation of mutants, structurally similar to their native isoform but inherently prone to amyloid conversion, may be a viable strategy to elucidate the structural features connected with amyloidogenesis. In this article, we present a computational protocol based on the combination of molecular dynamics (MD) and grid‐based approaches suited for the pairwise comparison of closely related protein structures. This method was applied on the cellular prion protein (PrPC) as a case study and, in particular, addressed to the quali/quantification of the structural features conferred by either E200K mutations and treatment with CaCl2, both able to induce the scrapie conversion of PrP. Several schemes of comparison were developed and applied to this case study, and made up suitable of application to other protein systems. At this purpose an in‐house python codes has been implemented that, together with the parallelization of the GRID force fields program, will spread the applicability of the proposed computational procedure. Proteins 2015; 83:1751–1765. © 2015 Wiley Periodicals, Inc.